PSYCHOSOCIOLINGUISTIC APPROACH TO STUDYING THE PROCESS CODE SWITCHING IN BILINGVAL ENVIRONMENT - E V Tutova (RUDN Journal of Language Studies, Semiotics and Semantics, 2017)
Linguists have recently started to explore code switching as a separate aspect. It can be more thoroughly traced in the speech of the bilinguals - people who can operate both languages equally and choose one of them in a suitable situation. However, linguists argue if code-switching is always moti-vated or are bilinguals influenced by the language factors.